Scientific Research Problems Facing Postgraduate Students (Masters) at the Faculty of Arts - Sebha University (Journal of Human Sciences, 2021)
The research aims to identify the most important scientific research problems that postgraduate students (masters) face, at the Faculty of Arts, Sebha University. It is conducted to know the statistical differences in scientific research problems attributed to the two variables (gender - scientific specialization). The sample included (50) students, who were chosen by the intentional sampling method. A questionnaire of scientific research problems prepared by Salima Elrashid was used. The results reached are that the most important scientific research problems facing graduate students are: research plan, analysis of results, formulation of hypotheses, research methodology and field procedures, statistical analysis, teaching staff members, students, the theoretical framework and previous studies, and finally the problem of references. There are statistically significant differences in the problems of scientific research that faces graduate students due to the variable of sex, and in favour of females. There are statistically significant differences attributed to the variable of scientific disciplines (Arabic language and Islamic studies, Psychology and Sociology). Ad there are no differences attributed to the scientific specialization variable (philosophy and history).